Life-span human development - Sigelman, Carol K. (Thomson/Wadsworth, 2006)
Written by text author Elizabeth Rider, the Study Guide includes a chapter review, learning objectives, a guided review including fill-in-the-blank and critical thinking questions, a review of key terms, a multiple-choice self-test, activity, application/essay questions, and an answer section for each chapter